2012
DOI: 10.1093/molehr/gas035
|View full text |Cite
|
Sign up to set email alerts
|

Specific genes are selectively expressed between cumulus and granulosa cells from individual human pre-ovulatory follicles

Abstract: During folliculogenesis, the granulosa cells differentiate into two cell types: cumulus cells (CCs) and mural granulosa cells (MGCs). The objective of the study was to generate and compare the transcriptomes of MGCs and CCs from the pre-ovulatory follicle to characterize the detailed profile of the two cell populations shortly before ovulation. Twenty-one IVF/ICSI patients undergoing controlled ovarian stimulation (COS) donated CCs and MGCs from individual follicles containing metaphase II oocytes. Cells were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 55 publications
(77 reference statements)
3
48
0
Order By: Relevance
“…MiR-383 promotes steroidogenesis by targeting RBMS1 via the inactivation of c-Myc [19]. These studies suggest that miRNAs are involved in the regulation of granulosa cell-related biological processes during folliculogenesis and emphasise the importance of the comparative identification of the miRNA profiles in CRCs and COCs [20][23].…”
Section: Introductionmentioning
confidence: 82%
“…MiR-383 promotes steroidogenesis by targeting RBMS1 via the inactivation of c-Myc [19]. These studies suggest that miRNAs are involved in the regulation of granulosa cell-related biological processes during folliculogenesis and emphasise the importance of the comparative identification of the miRNA profiles in CRCs and COCs [20][23].…”
Section: Introductionmentioning
confidence: 82%
“…With the inclusion of patients with tubal or unexplained cause of infertility, we excluded the possibility of gene expression differences deriving from primary disease such as PCO [36] or endometriosis [37, 38]. By analyzing individual GC and CC samples, we have gained detailed information about gene expression for each individual follicle, as it is known that pooling of samples can mask the detailed intrafollicular conditions [39]. Additionaly, by elective single embryo transfer we precisely knew which embryo did and which did not implant.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of human studies have shown correlations of CC gene expression with oocyte maturation, fertilization rate (McKenzie et al, 2004) and pregnancy outcome (Feuerstein et al, 2007;Hamel et al, 2008;Assou et al, 2010). However, all of these studies have used only CCs from pre-ovulatory follicles that were previously exposed to human chorionic gonadotrophin (hCG) (Kenigsberg et al, 2009;de los Santos et al, 2012;Grondahl et al, 2012) or CC derived from cumulus oocyte complexes (COCs) matured in vitro (Ouandaogo et al, 2012). We were unable to find any human study aimed at discerning differences in CC gene expression between immature COC derived from mid-antral follicles and COC obtained from mature follicles.…”
Section: Introductionmentioning
confidence: 99%